Fatores impactantes no resultado do ENADE em cursos de graduação em medicina - Anbar Neto, Toufic (2014)
Introduction: The evaluation of medical courses is still considered controversial by many higher education institutions (HEIs). The Brazilian National Student Performance Examination (ENADE) is an instrument used to measure the quality of undergraduate courses. The identification of factors that influence the result of this examination can contribute to providing support necessary to improve the quality of medical courses and, therefore, their rating in ENADE. Objective: To assess factors that impact on the ENADE outcomes of graduate and undergraduate medical courses in respect to academic, educational and demographic variables and the infrastructure of the local healthcare system. Material and Method: Factors that influenced the ENADE outcomes obtained by 136 medical courses in 2010 were investigated. The data were collected from databases and spreadsheets of the Ministry of education. Demographic (geographic location), and educational and academic variables (academic organization, age of course, number of places, qualifications of faculty members, course load hours, strictu sensu post-graduation program, administrative category and teaching methodology) were investigated as was the infrastructure of the local healthcare system [total number of beds and beds dedicated to Brazilian National Health Service (SUS) patients in the municipal of the medical school]. Data analysis was based on the performance of medical courses in the ENADE in 2010. Courses were divided into two groups: ENADE Grades 1-2 (negative rating) versus ENADE Grades 4-5 (positive rating). Results: Most medical courses (82.9%) belonging to larger universities obtained Grades 4 or 5. The time of existence of courses was greater in the ENADE Grade 4-5 Group (median: 43 years). The number of places was higher in the ENADE Grade 1-2 Group (median: 100). There was a predominance of faculty members with masters and doctors degrees in the ENADE Grade 4-5 Group. The course load hours was slightly higher in the ENADE Grade 4-5 Group (median: 8400 hours). Most courses (93.4%) with strictu sensu postgraduate programs obtained Grades 4 or 5. Most courses (96.3%) belonging to public HEIs obtained Grades 4 or 5. Most courses (76.3%) that used traditional teaching methodology obtained Grades 4 or 5. The number of NHS beds/1000 inhabitants was lower in the ENADE Grade 1-2 Group than in the ENADE Grade 4-5 Group (median: 2.24 vs. 2.34). The number of total beds/1000 inhabitants was lower in the ENADE Grade 1-2 Group in relation to ENADE Grade 4-5 Group (median: 3.41 vs. 3.95). Conclusions: Factors that positively impacted on ENADE outcomes for medical courses include being part of larger universities, older courses, fewer students, predominance of staff with master's and doctoral degrees, having a strictu sensu postgraduate program, being a public HEIs and higher numbers of total beds and beds dedicated to NHS patients in the municipal.